Comprehensive analysis of mixed neuroendocrine non-neuroendocrine neoplasms (MiNENs): A SEER database analysis of 767 cases - Song, Huixin; Yang, Sen; Zhang, Yalu; Hua, Yuze; Kleeff, Jorg; Liu, Qiaofei; Liao, Quan (Frontiers in Oncology, 2023)
Background Mixed neuroendocrine non-neuroendocrine neoplasm (MiNEN) is an extremely rare entity, consisting of neuroendocrine and non-neuroendocrine components, with a rising incidence. Its clinical management is a rapidly growing field of interest; however, large-scale patient cohorts are still missing to guide clinical practice. Patients and methods The demographic, clinicopathological, and survival information of all patients diagnosed with MiNEN in the SEER program database (2000–2017) were extracted and further analyzed. The characteristics of MiNEN originating in different organs were compared. The clinical significance of surgical resection for metastatic MiNENs was also analyzed. Results A total of 1081 patients were screened 767 patients were finally analyzed. There was no obvious sex preference (49.2% vs 50.8%, p>0.05) and the majority of the patients were Caucasians (n=627, 81.7%). A total of 88.3% of the patients were older than 50 years old, and the median age was 60 years. 79.3% of the tumors are located in the distal digestive tract, and 67.7% were grade 3/4. Distant metastasis was presented in 33.9% of the patients at diagnosis. A total of 88% of the patients underwent surgical treatments. The number of patients increased 10-fold between 2000 and 2017. There was no significant difference in sex, race, stage, or surgical treatments among the patients diagnosed before and after 2010. More patients older than 60 years were diagnosed after 2010 (p=0.009). The median survival was 61.0±9.8 months for the whole cohort. After multivariate analysis, older age (>60 years, p<0.01), more advanced stage (p<0.01), grade 3/4 (p<0.01), and non-surgical treatment (p<0.01) were independent risk factors for poorer survival. The appendiceal MiNENs showed the best prognosis. Only patients with metastatic MiNENs originating from the appendix had a potential benefit from surgical resection, compared to other sites (p=0.05). Conclusion: This study provides the epidemiological, clinicopathological, and survival information of the largest number of MiNEN patients. The majority of the patients suffered from advanced-stage disease, which highlights the need for improvement of early detection in the future. The appendix is the most common primary site of MiNEN, and surgical resection for selected metastatic MiNEN originating in the appendix has favorable survival outcomes.